The Acquisition of Tense and Agreement - Torrens, Vicenç (Cambridge Scholars Publisher, 2020)
This book presents research on the acquisition of Tense and Agreement in Spanish and Catalan, describing the different theoretical explanations of this process. Its theory is drawn from the Minimalism Program, which proposes Universal Principles for all languages and the existence of parameters that can take different values in particular languages. The study describes the acquisition of root infinitives, subject-verb agreement, the position of clitic pronouns with respect to finite and non-finite verbs, the placement of negation, the position of subjects, and the acquisition of personal prono.